Clinical experience of a new reference material for exercise capacity in exercise stress testing in Sweden. (21st September 2017) - Lindow, Thomas; Mosén, Henrik; Engblom, Henrik
Summary: Background: In 2014, the Swedish Association of Clinical Physiology recommended the use of a new reference material for exercise capacity in bicycle exercise stress testing, 'the Kalmar material'. Compared to the formerly used reference material, 'the Kristianstad material', an increase in the amount of patients being classified as having decreased exercise capacity was expected, but the extent of this in clinical practice is not known. Methods: Results of exercise capacity from 1449 bicycle exercise tests, in patients aged ≥20 years (656 women, 793 men) performed at two departments of Clinical Physiology before and after change of reference materials, were collected. Maximal workload was related to the predicted values of both reference materials. If made, recommendations for supplemental nuclear myocardial perfusion imaging study by the attending physician were noted. Results: Using the new reference material, 31% of all patients were classified as having a decreased exercise capacity, compared to 17% using the formerly used reference material. The difference between the two reference materials was largest in the older age groups. In one of the departments, an increase in recommendations of supplemental myocardial perfusion studies was seen after introduction of the new reference material, whereas the opposite was seen at the other department. Conclusion: A large amount of patients are being classified as having decreased exercise capacity and very few as having good exercise capacity using the new reference material for exercise capacity.